Perilaku Hidup Sehat Terhadap Tingkat Kesegaran Jasmani Siswa Kelas XI IPA 2 SMA Negeri 9 Semarang T/A 2019/2020 (Universitas Negeri Semarang, 2021)
The background of this research is the modernization era as it is today physical freshness is the main capital that should be owned by a person, be it adults or children. This research uses quantitative methods. The location of this research is in Semarang City with a research population of grade XI IPA 2 students of SMA Negeri 9 Semarang as many as 30 students, with census sampling techniques. The data collection instrument is conducted using questionnaires and freshness tests. The data analysis methods used are validity test, reliability test, normality test, linearity test, and product moment analysis. The results of this study showed that healthy living behavior variables have a significant positive influence simultaneously on physical health variables. The result of the analysis obtained a correlation coefficient value (r hit) of 0.848 > r tab 0.361. The conclusion of this research is that the implementation of sports activities of SMA N 9 Semarang went well. The advice given is that schools should provide sports facilities and infrastructure and provide more support to students to develop their talents.